An Overview Regarding Obesity Rate in European Union Countries - Petrariu Ileana (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2021)
The purpose of the research is to highlight the evolution of overweight and obesity epidemic on EU countries, it’s social and economical impact, risk factors and complications. Data demonstrates that obesity epidemic level are rising. The prognostics require society and public healthcare professionals’ immediate resolutions